Influence of Lanthanum Concentration on Microstructure of (Ho1–xLax)2O3 Magneto‐Optical Ceramics. Issue 8 (18th February 2020) - Balabanov, Stanislav; Demidova, Kristina; Filofeev, Sergey; Ivanov, Maxim; Kuznetsov, Dmitrii; Li, Jiang; Permin, Dmitry; Rostokina, Elena
Abstract : Transparent cubic‐phase solid solution (Ho1– x La x )2 O3 (where x  = 0, 0.03, 0.05, 0.07, and 0.1) ceramics are sintered in a vacuum at 1780 °C for 3 h from nanopowders made by self‐propagating high‐temperature synthesis. The lanthana is proved to significantly influence the microstructure of the ceramics. The average crystallite sizes of the (Ho1– x La x )2 O3 ceramics decrease with an increase in the concentration of lanthana. After vacuum sintering and low‐temperature annealing in air, the ceramics have second‐phase grains at the crystallite boundaries and the triple points. The volume fraction of the second phase is found to be in direct proportion to the lanthana content in the ceramics. This second phase is believed to be (Ho1– x La x )2 O3 solid solutions with a higher lanthanum content in comparison with the surrounding crystallites. Annealing of the ceramics at 1500 °C for 2 h leads to the elimination of the second phase. Abstract : Transparent cubic‐phase (Ho1– x La x )2 O3 solid solution ceramics with lanthanum content up to 10 mol% are sintered in vacuum from nanopowders made by self‐propagating high‐temperature synthesis. After sintering and annealing in air, the ceramics have second phase at crystallite boundaries and triple points. A structure of the second phase and ways to eliminate it are shown in the research.